Mapping knowledge landscapes and emerging trends in digital biomarkers for dementia in older adults: A scoping and bibliometric analysis - Azliyana Azizan; Shihua Cao; Akehsan Dahlan; Susi Endrini (Archives of Gerontology and Geriatrics Plus)
This paper presents a systematic bibliometric analysis of the research landscape at the intersection of Alzheimer's disease and gerontechnology, identifying key contributors, research hotspots, and emerging trends. Utilizing data from Scopus and Web of Science, the study applies tools such as VOSviewer and ScientoPy to analyze co-authorship networks, keyword occurrences, and citation trends. The results reveal growing contributions from global regions, particularly the U.S., Italy, and China, with increasing emphasis on assistive technologies and artificial intelligence for early diagnosis. However, significant gaps exist, especially in studies addressing long-term effectiveness and inclusivity across demographic groups. This landscape analysis provides crucial insights to guide future research on integrating technology into Alzheimer's care, underscoring the importance of a patient-centered approach for sustainable solutions.